3D sandwich-type prostate specific antigen (PSA) immunosensor based on rGO–MWCNT–Pd nanocomposite. (26th May 2015) - Tian, Lihui; Liu, Lei; Li, Yueyuan; Wei, Qin; Cao, Wei
Abstract : A signal amplifying sandwich-type immunosensor with a wide linear range and a low detection limit is developed with potential clinical and diagnostic applications. Abstract : In this work, a novel and ultrasensitive sandwich-type electrochemical immunosensor was developed for the quantitative detection of prostate specific antigen (PSA), a well-known prostatic tumor biomarker. A 3D-structured reduced graphene oxide–multiwalled carbon nanotube–palladium nanoparticle (NP) nanocomposite (rGO–MWCNT–Pd) was prepared in a simple and environmentally friendly way and utilized for the adsorption of secondary antibodies (Ab2 ). It is used as a novel enzyme-mimicking label to develop a sandwich-type electrochemical immunosensor for signal amplification, and shows better electrocatalytic activity for the reduction of hydrogen peroxide (H2 O2 ) than rGO–CNT or rGO–Pd due to the synergetic effect of the rGO–MWCNT–Pd nanocomposite. The nanocomposite of Au NPs decorated on aminated graphene (Au–NH2 –GS) is used as a platform for the immobilization of primary antibobies (Ab1 ) via an amide reaction between the –NH2 group of the Au–NH2 –GS and the –COOH groups of Ab1 . Due to the excellent electrocatalytic activity of rGO–MWCNT–Pd for the reduction of H2 O2, electrochemical amperometric changes at different concentrations of PSA were studied after the immunoreaction. Under the optimum experimental conditions, the proposed electrochemical sandwich-type immunosensor exhibits a low detection limit (0.17 pg mL −1 ), and a wide linear range (from 0.5 pg mL −1 to 15 ng mL −1 ) for the detection of PSA. It also shows high sensitivity, good selectivity and stability, and has great potential in clinical and diagnostic applications.